2017
DOI: 10.1111/1751-7915.12710
|View full text |Cite
|
Sign up to set email alerts
|

Microbial enzymes for the recycling of recalcitrant petroleum‐based plastics: how far are we?

Abstract: SummaryPetroleum‐based plastics have replaced many natural materials in their former applications. With their excellent properties, they have found widespread uses in almost every area of human life. However, the high recalcitrance of many synthetic plastics results in their long persistence in the environment, and the growing amount of plastic waste ending up in landfills and in the oceans has become a global concern. In recent years, a number of microbial enzymes capable of modifying or degrading recalcitran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
394
1
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 606 publications
(402 citation statements)
references
References 175 publications
3
394
1
4
Order By: Relevance
“…For example, cutinase from Fusarium solani pisi (FsC) is a promising candidate for the enzymatic degradation of PET; another special enzyme from leaf‐branch compost metagenome (LC cutinase, LCC) can break down PET, cutin, and polycaprolactone (PCL); and the hydrolases from Thermobifida fusca (TfH) has prominent activity on polyester hydrolysis . However, even though the levels of activity can be maintained up to 50–70 °C, cutinase has extremely low turnover rates towards a highly aggregated PET substrate . Although protein‐engineering strategies have been applied to enhance the activity of cutinase, the continuous mining of new PET hydrolases with highly efficiency and specificity towards polyesters is an alternative strategy for enzymatic hydrolysis of PET …”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…For example, cutinase from Fusarium solani pisi (FsC) is a promising candidate for the enzymatic degradation of PET; another special enzyme from leaf‐branch compost metagenome (LC cutinase, LCC) can break down PET, cutin, and polycaprolactone (PCL); and the hydrolases from Thermobifida fusca (TfH) has prominent activity on polyester hydrolysis . However, even though the levels of activity can be maintained up to 50–70 °C, cutinase has extremely low turnover rates towards a highly aggregated PET substrate . Although protein‐engineering strategies have been applied to enhance the activity of cutinase, the continuous mining of new PET hydrolases with highly efficiency and specificity towards polyesters is an alternative strategy for enzymatic hydrolysis of PET …”
Section: Figurementioning
confidence: 99%
“…However, even though the levels of activity can be maintained up to 50–70 °C, cutinase has extremely low turnover rates towards a highly aggregated PET substrate . Although protein‐engineering strategies have been applied to enhance the activity of cutinase, the continuous mining of new PET hydrolases with highly efficiency and specificity towards polyesters is an alternative strategy for enzymatic hydrolysis of PET …”
Section: Figurementioning
confidence: 99%
“…These include bacteria in the gut of the wax worm Plodia interpunctella capable of degrading polyethylene (PE) (Yang et al ., ; Bombelli et al ., ) and the bacterium Ideonella sakaiensis , which can depolymerize poly(ethylene terephthalate) (PET) and grow on the resulting terephthalate component (Yoshida et al ., ). The identification and engineering of plastic‐degrading organisms and enzymes provide a compelling opportunity to increase plastic recycling and thereby reduce plastic pollution through the utilization of plastic waste as carbon source for microbial biotechnology (Cho et al ., ; Wierckx et al ., ; Narancic and O'Connor, ; Wei and Zimmermann, , ; Austin et al ., ).…”
Section: Introductionmentioning
confidence: 98%
“…To be sure, the carbon-carbon backbones of many common plastic polymers make them more resistant to enzymatic breakdown than many biological materials (Wei & Zimmermann, 2017) and some types of plastic may be virtually unchanged even after decades of burial (Otake, Kobayashi, Asabe, Murakami, & Ono, 1995). However, exposure to the elements, particularly ultraviolet radiation, may sensitize some plastics to microbial colonization and biodegradation (Gong, Yang, Zhuang, & Zeng, 2019;Vimala & Mathew, 2016;Wei & Zimmermann, 2017), and Otake et al (1995) reported that polyethylene films were heavily degraded after years of burial. Numerous soil microbes, both bacteria and fungi, have been implicated in plastic degradation (Kale et al, 2015;Shah et al, 2008;Yoshida et al, 2016).…”
Section: Crob Ial Effec Ts: Coloniz Ati On and Deg R Adationmentioning
confidence: 99%